Mullerian duct anomalies presenting with primary amenorrhoea - Chandrayan, Piyusha; Parekh, Usha; Jain, Niyati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Primary amenorrhoea is defined as the absence of menstruation by 14 years of age when there is no visible development of secondary sexual characteristics or by 16 years of age in the presence of normal secondary sexual characteristics. Primary Amenorrhoea occurs if there is a blockage of the outflow tract, or the outflow tract is missing, or there is no functioning uterus. The causes include: Transverse blockages, Mullerian Anomalies, and absence of functioning endometrium. The true incidence of obstructive Müllerian anomalies is unknown, but is believed to be between 0.1% and 3.8%.The second most common cause of primary amenorrhoea is mullerian anomaly. The aim of this study is to find the most common cause of primary amenorrhoea among mullerian anomalies and its renal association, the presenting symptom and the modalities to investigate it. Methods: After obtaining approval from the ethical committee, a retrospective study was undertaken of all cases of primary amenorrhoea presented at Dhiraj General Hospital, affiliated to SBKS Medical college and research centre, Waghodiya during a 5 year period (June 2011-June 2015). In inclusion criteria, all non-pregnant women of Reproductive age group attending Gynaecology O.P.D. at Dhiraj General Hospital with complains of primary amenorrhoea with normal secondary sex characters were included in the study (June 2011-June 2015). In exclusion criteria, after the detailed investigations, all non-pregnant women with complain of primary amenorrhoea due to any other cause than mullerian anomaly were excluded. Results: In this study, most of the patients belonged to Class I, i.e. these patients had absent uterus, cervix and fallopian tubes along with upper part of vagina(61.5%) consisting of MRKH type 1. Nearly, 31% belonged to class II type; these patients had transverse vaginal septum with or without uterine anomaly. One patient belonged to class III type, (7.6%) i.e. imperforate hymen with hematocolpos and hematometra. Conclusions: We conclude that Mayer-Rokitansky-Kuster-Hauser syndrome (MRKH) with normal female secondary sexual development is the commonest cause of primary amenorrhea in our study.